The Effectiveness of Project Based Learning (PJBL) in Improving Volleyball Upper Passing: A Case Study at SMP Negeri 3 Satu Atap - Nasution, Muhammad Alfa Himawan; Riza, Ade Ros; Simbolon, Dicky Bastian; Samudra, Bayu; Lubis, Irwansyah Hafidh; Habibi, Muhammad Iqbal; Ridoh, Muhammad (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to analyze or determine whether the provision of project based learning (PJBL) model can improve student learning outcomes. The research method used is Classroom Action Research. The subjects of this study were grade VII students at SMP Negeri 3 Satu Atap Aek Natas with a total of 34 students, consisting of 14 male students and 20 female students. Based on the research conducted, the results of the study in cycle I were 20 students with a converted score of (58.82%) who had achieved the level of learning completion, while 14 students (41.18%) had not achieved the level of learning completion, with an overall average score of 69.83, while in cycle II, data was obtained from 30 students with a converted score of (88.24%) who had achieved completion in learning, while 4 students (11.76%) were still incomplete, with an average learning outcome score of 78.68. Based on the results of the test, there was an increase in the number of students who had achieved learning completion and met the Classical Completion Criteria, namely 85%. Based on the results of the data analysis, it can be concluded that the application of the Project Based Learning (PJBL) Learning model given by researchers to teachers and students has a positive impact and can improve the learning outcomes of volleyball passing at SMP Negeri 3 Satu Atap Aek Natas.